Structural and functional insights into recombinant β-glucosidase from Thermothelomyces thermophilus: Cello-oligosaccharide hydrolysis and thermostability - Saraiva, Ana Luiza da Rocha Fortes; Berto, Gabriela Leila; Oliva, Bianca; Cunha, Paula Macedo; Ramos, Lucas; de Oliveira, Leandro Cristante [UNESP]; Segato, Fernando (Elsevier, 2025)
β-glucosidases (BGLs) are key enzymes in the depolymerization of cellulosic biomass, catalyzing the conversion of cello-oligosaccharides into glucose. This conversion is pivotal for enhancing the production of second-generation ethanol or other value-added products in biorefineries. However, the process is often cost-prohibitive due to the high enzyme loadings required. Therefore, the discovery of new highly efficient BGLs represents a significant advancement. In this study, a BGL from the glycoside hydrolase family 3 (GH3) of the thermophilic fungus Thermothelomyces thermophilus (TthBgl3A) was heterologously expressed in Aspergillus nidulans. The recombinant enzyme exhibited optimal activity at pH 5.0 and 55 °C, with noteworthy stability for up to 160 h. A distinctive, extensive loop within the catalytic cavity of TthBgl3A facilitates hydrophobic interactions that enhance the binding and hydrolysis of long cello-oligosaccharides. Consequently, TthBgl3A has proven to be an efficient enzyme for the hydrolysis lignocellulosic biomass. These findings are significant for expanding the repertoire of enzymes produced by T. thermophilus and provide new insights into the potential application of TthBgl3A in the degradation of cellulosic materials and the production of valuable compounds.
Keywords: Cello-oligosaccharides affinity; Cellulolytic cocktail; Enzymatic hydrolysis; Kinetics; Molecular dynamics; Sugarcane bagasse; Thermostable enzymes